Using a Flipped Classroom to Teach Evidence-Based Practice to Entry-Level Occupational Therapy Students - April C. Cowan; Karen Ratcliff; Chih-Ying Li (Journal of Occupational Therapy Education, 2023)
Constructivist teaching approaches rely on students to be active participants in their learning. A flipped classroom is a constructivist approach that requires the students to complete pre-learning activities outside of class. Thus, in class the students can practice and engage in team-based discussions and teacher guided learning. We delivered evidence-based practice (EBP) concepts to entry level occupational therapy (OT) students in a doctoral program using a constructivist approach, that included a flipped classroom model and reliance on team-based strategies. We used the Evidence Based Practice Confidence (EPIC) Scale to assess the change in students’ confidence in EBP. Students demonstrated statistically significant differences in their confidence for EBP after the course. Evaluation of the changes in EPIC Scale scores indicates that a flipped classroom and team-based activities are effective approaches to teach EBP for entry level OT doctoral students.